Contribution to the physical study of the tablets: Hardness tests. Tablets from the national pharmaceutical market - Herráez, M.; Suñé, J.Mª. (Ars Pharmaceutica (Internet), 1967)
In this first communication thirty samples of isoniazid tablets of the Spanish pharmaceutical market are tested, and the experimental results were submitted to a stadistical study. Amongst results of some interest, there are ones which arrived at the fact that 10% of the samples should revise their formulas to diminish the content of auxiliary substances; acceptable values of hardness and disintegration are found for all the samples; and it was found that in 13% of the cases the error in active substance is superior to 10%, with respect to the theoric content and is therefore not considered accetable.